Sami and the Time of the Troubles - Florence Parry Heide (Houghton Mifflin Harcourt Publishing Company, 1995)
A ten-year-old Lebanese boy balances his life in a war-torn city. "Lewin's watercolor illustrations capture contemporary Beirut with stunning clarity and drama . . . Unforgettable." -- School Library Journal, starred review
Keywords: Peace, Justice And strong Institutions; Circle Time - Refugees / War Stories / Immigrants -- Circle Time - Refugees / War Stories / Immigrants